Molecular detection of Borrelia burgdorferi (sensu lato) and Rickettsia spp. in hard ticks distributed in Tokachi District, eastern Hokkaido, Japan - Kiyoshi Okado; Paul Franck Adjou Moumouni; Seung-Hun Lee; Thillaiampalam Sivakumar; Naoaki Yokoyama; Kozo Fujisaki; Hiroshi Suzuki; Xuenan Xuan; Rika Umemiya-Shirafuji (Current Research in Parasitology and Vector-Borne Diseases, 2021)
Ticks transmit various pathogens, including parasites, bacteria and viruses to humans and animals. To investigate the ticks and the potentially zoonotic pathogens that they may carry, questing ticks were collected in 2017 from 7 sites in Tokachi District, eastern Hokkaido, Japan. A total of 1563 ticks including adults (male and female), nymphs and larvae were collected. Four species of ticks were identified: Ixodes ovatus, Ixodes persulcatus, Haemaphysalis japonica and Haemaphysalis megaspinosa. Of the 1563 ticks, 1155 were used for DNA extraction. In total, 527 individual tick DNA samples prepared from adults (n = 484), nymphs (n = 41) and larvae (n = 2); and 67 pooled tick DNA samples prepared from larval stages (n = 628) were examined using PCR methods and sequencing to detect Borrelia burgdorferi (sensu lato) and Rickettsia spp. The phylogenetic analysis of Borrelia spp. flaB gene sequences showed the presence of the human pathogenic B. burgdorferi (s.l.) species (Borrelia garinii, Borrelia bavariensis and Borrelia afzelii) in I. persulcatus, whereas the non-pathogenic species Borrelia japonica was found only in I. ovatus. In I. persulcatus, B. garinii and/or its closely related species B. bavariensis was detected in both adults and nymphs at a prevalence of 21.9% whereas B. afzelii was found only in adults (1.8%). The prevalence of B. japonica in adult I. ovatus was 21.8%. Rickettsia species were identified through phylogenetic analysis based on gltA, 16S rRNA, ompB and sca4 genes. Four genotypes were detected in the samples which were classified into three species. The prevalence of human pathogenic Rickettsia helvetica was 26.0% in I. persulcatus adults and nymphs, 55.6% in I. persulcatus larval pools, and 1.7% in H. megaspinosa larval pools. The prevalence of “Candidatus R. tarasevichiae” was 15.4% in I. persulcatus adults and nymphs and 33.3% in I. persulcatus larval pools. The prevalence of “Candidatus R. principis” in H. megaspinosa adults and nymphs was 11.1% whereas it was detected in 3.4% of the H. megaspinosa larval pools. These results indicate that most of the risks of Lyme borreliosis and spotted fever group rickettsiosis infection in eastern Hokkaido, Japan, are restricted to I. persulcatus.